Ciliated epithelia are key elements in the recruitment of bacterial partners in the squid-vibrio symbiosis - Gundlach, Katrina A.; Nawroth, Janna; Kanso, Eva; Nasrin, Farzana; Ruby, Edward G.; McFall-Ngai, Margaret (Frontiers in Cell and Developmental Biology, 2022)
The Hawaiian bobtail squid, Euprymna scolopes, harvests its luminous symbiont, Vibrio fischeri, from the surrounding seawater within hours of hatching. During embryogenesis, the host animal develops a nascent light organ with ciliated fields on each lateral surface. We hypothesized that these fields function to increase the efficiency of symbiont colonization of host tissues. Within minutes of hatching from the egg, the host’s ciliated fields shed copious amounts of mucus in a non-specific response to bacterial surface molecules, specifically peptidoglycan (PGN), from the bacterioplankton in the surrounding seawater. Experimental manipulation of the system provided evidence that nitric oxide in the mucus drives an increase in ciliary beat frequency (CBF), and exposure to even small numbers of V. fischeri cells for short periods resulted in an additional increase in CBF. These results indicate that the light-organ ciliated fields respond specifically, sensitively, and rapidly, to the presence of nonspecific PGN as well as symbiont cells in the ambient seawater. Notably, the study provides the first evidence that this induction of an increase in CBF occurs as part of a thus far undiscovered initial phase in colonization of the squid host by its symbiont, i.e., host recognition of V. fischeri cues in the environment within minutes. Using a biophysics-based mathematical analysis, we showed that this rapid induction of increased CBF, while accelerating bacterial advection, is unlikely to be signaled by V. fischeri cells interacting directly with the organ surface. These overall changes in CBF were shown to significantly impact the efficiency of V. fischeri colonization of the host organ. Further, once V. fischeri has fully colonized the host tissues, i.e., about 12–24 h after initial host-symbiont interactions, the symbionts drove an attenuation of mucus shedding from the ciliated fields, concomitant with an attenuation of the CBF. Taken together, these findings offer a window into the very first interactions of ciliated surfaces with their coevolved microbial partners.